Evaluation of Wastewater Treatment Plant Operating Extended Aeration and Nutrients Removal - Hiba Mohammad (Waste Technology, 2019)
Construction of Rwaymiah Waste Water Treatment Plant, (WWTP) in city of Lattakia, Syria since 2011 but until recently it still lacks a continuous   evaluation of the performance.  WWTP performance evaluation is needed to see how far the efficiency of processing result. This research aims to assess the treatment efficiency and the quality of the final effluent in accordance with the required design standards for Rwaymiah wastewater treatment plant in Lattakia city, working in extended aeration combined with biological nutrients removal (BNR) technology. Laboratory analyzes and measurements periodically for period of the month of January 2013 until the end of January of the year 2016 were conducted for the indicators: biochemical oxygen demand (BOD), total suspended solids (TSS), nitrate (NO3-), phosphate (PO4-3). The results showed that the efficiency of the treatment was good to treat BOD5 and TSS at Rwaymiah WWTP and the final effluent achieved all the required design criteria, average in plant. However, the final effluent did not achieve all the required design criteria of NO3  and PO4-3. In this research, we recommend to the need for periodic measurements at each plant for pollution indicators in order to monitor and adjust the efficiency of treatment facilities